IMPLEMENTATION OF THE INTERNATIONAL PLANT PROTECTION CONVENTION (IPPC) IN THE REGULATION OF THE AGREEMENT ON THE APPLICATION OF SANITARY AND PHYTOSANITARY MEASURES (SPS AGREEMENT) IN THE WORLD TRADE ORGANIZATION (WTO): NOTES TO INDONESIA - Afriansyah, Arie; Ardiastuti, Elisabeth (Yustisia, 2017)
World Trade Organization (WTO) is an international organization which has an important role in ensuring that the flow of global trade can run with as few barriers as possible. However, according to Article XX (b) of GATT, the WTO members may apply trade measures in order to protect human, animal or plants life or health. Agreement on the Application of Sanitary and Phytosanitary Measures (SPS Agreement) is an elaboration of the provision of Article XX (b) of GATT. According to the SPSA greement, the WTO members have the right to apply measures necessary to protect human, animal or plant life or health, based on sufficient scientific principles and scientific evidences, as well as not constituting arbitrary discrimination or a disguised restriction on international trade. Fulfilment of the scientific and technical needs in the application of the SPS Agreement, the SPS Agreement refers to International Plant Protection Convention (IPPC) as the relevant international organization for promoting the harmonization of phytosanitary measures based on international standards adopted by IPPC. This article discusses the application of the SPS Agreement and IPPC in three WTO cases, i.e. Japan – Agricultural Products II (2001), Japan – Apples (2005) and Australia – Apples (2011).